Ethnic fragmentation and school provision in India - Nishant Chadha; Bharti Nandwani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
In this paper, we study the impact of ethnic fragmentation on the provision of private and public schools, separately. The distinction is made because the two types of schools have different objective functions, a factor which can influence the relationship between ethnic fragmentation and public goods provision. We find that ethnic fragmentation has a negative impact on the provision of schools overall, but this effect manifests differently for the two types of schools considered. To explain our findings we show that ethnic fragmentation lowers collective action, and because of the different objectives of provision of private and public schools, lack of collective action results in a differential impact. While private schools are shown to be lower in number, public schools are of lower quality in fragmented districts.
Keywords: H4; O2; I0; 330; Ethnic fragmentation; private schools; public good provision; public schools